A study on the effects of service quality on customer satisfaction towards bus transit in Malacca Central / Siti Aisyah Ishak and Nurul Hidayah Moktarroji - Ishak, Siti Aisyah; Moktarroji, Nurul Hidayah (Faculty of Administrative Science and Policy Studies, 2013)
Our research project paper title is ‘A Study on the Effects of Service Quality on Customer Satisfaction towards Bus Transit in Melaka Central’. We want to study about the customer satisfaction toward bus transit because the issue raising which the customers is not satisfied with the services that bus transit organization deliver to them. Our research objective is to determine the service quality attributes that affects public satisfaction toward bus transit in Malacca city, to investigate which attribute is the most significant that lead to customer satisfaction toward bus transit in Malacca city, to investigate which attribute is the less significant to customer satisfaction toward bus transit, and to make some recommendation on how the bus transit system in Malacca can be improved. Our research method is from the Melaka Central; a convenience sampling of 200 respondents will be selected and surveyed to determine any relationship between the services quality attributes with the level of satisfaction of customers. The questionnaire will be distributed to the respondent to get information about their level of satisfaction towards the bus transit. Other than that in this research, an opinion will be requested from the respondent in order to get some information and recommendation. Data will be analyzed using the statistical correlations between measured variables.